2019
DOI: 10.1080/10903127.2019.1568651
|View full text |Cite
|
Sign up to set email alerts
|

Existing Science on Human Factors and Ergonomics in the Design of Ambulances and EMS Equipment

Abstract: Background: Emergency medical services (EMS) personnel face a disproportionally high risk for fatality and injury due to the nature of their work; and current ambulance and EMS equipment design standards do not adequately safeguard EMS personnel from sacrificing personal safety for patient care, a known human factors and ergonomic (HFE) design challenge. Despite the desire to include HFE interventions or considerations into a standard, the effectiveness of existing HFE interventions for EMS is unclear. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Standards and guidelines may be lacking in the following areas: evidence-based data (due to availability), full transparency (conflict of interest in development), scientifically supported methods (controlling for confounding factors, understanding combined and interactive effects), and sensitivity and specificity of threshold values for numerous potential effects [47]. However, when evidence-informed standards and guidelines are well-designed and implemented, their impact has been shown to potentially reduce workplace injuries [38,48,49] and have positive impacts on an organisation's safety, operational and economic performance [50]. For instance, a study by Yung et al [49] evaluated the impact of the new 2018 American Conference of Governmental Industrial Hygienists (ACGIH) guideline for intensive hand activities in manufacturing; authors found in a large US prospective cohort study that this new guideline, when implemented, can prevent between 11% and 25% of cases of Carpal tunnel syndrome in the cohort.…”
Section: Prevention Measures That Can Be Taken In the Workplacementioning
confidence: 99%
“…Standards and guidelines may be lacking in the following areas: evidence-based data (due to availability), full transparency (conflict of interest in development), scientifically supported methods (controlling for confounding factors, understanding combined and interactive effects), and sensitivity and specificity of threshold values for numerous potential effects [47]. However, when evidence-informed standards and guidelines are well-designed and implemented, their impact has been shown to potentially reduce workplace injuries [38,48,49] and have positive impacts on an organisation's safety, operational and economic performance [50]. For instance, a study by Yung et al [49] evaluated the impact of the new 2018 American Conference of Governmental Industrial Hygienists (ACGIH) guideline for intensive hand activities in manufacturing; authors found in a large US prospective cohort study that this new guideline, when implemented, can prevent between 11% and 25% of cases of Carpal tunnel syndrome in the cohort.…”
Section: Prevention Measures That Can Be Taken In the Workplacementioning
confidence: 99%
“…Patient care during transport is an inherent feature of driving an ambulance. However, this unavoidable element of the job puts ambulance personnel at a higher risk of crash [ 30 ], albeit that the most serious and fatal injuries occur in the rear compartment of an ambulance [ 31 ]. Ambulance design is not directed to occupant protection, and elements such as sharp edges on cabinets, poorly designed seatbelts, and the risk of projectiles put personnel and other occupants at higher risk of injury in a crash [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this unavoidable element of the job puts ambulance personnel at a higher risk of crash [ 30 ], albeit that the most serious and fatal injuries occur in the rear compartment of an ambulance [ 31 ]. Ambulance design is not directed to occupant protection, and elements such as sharp edges on cabinets, poorly designed seatbelts, and the risk of projectiles put personnel and other occupants at higher risk of injury in a crash [ 30 , 31 ]. Although concerns about the design of ambulances have been documented in earlier studies and improved design recommended [ 22 ], more recent work shows that newer ambulances are not safer for ESV personnel and occupants [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how paramedics work within an ambulance may address inefficiencies in design and functionality that contribute to the potential for injury to the paramedic and compromise patient care. 19 Limitations This study has a number of limitations. First, the participants were paramedic students rather than experienced and qualified paramedics.…”
mentioning
confidence: 99%